Study on the Stirring Device of Vinyl Polymers - Zhiqiang ZHU; Fanglin JIANG; Yangyong MAO; Jianfeng WU; Qingwei JIANG; Sujie JIANG (Pige Kexue Yu Gongcheng)
Vinyl polymers are a new type of polymer characterized by high solubility, low viscosity under normal conditions, a majority of terminal functional groups, and cavities within their molecular structure, making them highly valuable in applications such as leather tanning agents. The stirring process during the preparation of vinyl polymers greatly affects the performance of the polymers. Commonly used reaction devices, when faced with varying viscosities of materials at different reaction stages, cannot adjust the stirring method and intensity, leading to poor performance of the resulting polymer. This article analyzed the impact of the stirring devices in chemical industry reactors, which are commonly used for the polymerization process of vinyl synthetic resins, and explored an improved stirring device for polymerization reactors based on existing theories and practical factory experience.